Web Based Social Assistance Distribution Monitoring System Using Waterfall Method - Jihan Ula Usla; Ali Ikhwan (Information Technology and Science (ITScience), 2023)
Currently, the Indonesian nation is in a state of economic crisis, many people are affected by the economic crisis. Social assistance is the provision of assistance in the form of money/goods from the government to underprivileged communities, which aims to improve people's welfare and meet the needs of the community in maintaining their lives during the current economic crisis. The village head is one of the government officials as well as officers from the social assistance distribution with the aim of minimizing the problem. A lot of assistance comes but is not evenly distributed to people in need, it is necessary to have a monitoring system for the distribution of social aid programs so that the assistance distributed remains on target and the quality of budget absorption is optimal. The monitoring process will be carried out by the village head directly to monitor the progress of the distribution of aid and submissions. Therefore, this research will build a web-based monitoring system for the distribution of social assistance. This social assistance distribution system in the form of a website, will contain data on recipients of the family hope program and community submission data. The design of this system uses Unified Modeling Language (UML) and the development of the system uses the Waterfall method which will test the system. With this system, it will help the Village Head in monitoring the distribution of aid and assist the community in submitting it.